The Role of Collaboration Strategy and Regulation in Enhancing the Competitiveness of Legal Products: The Mediating Effect of Regulatory Effectiveness - Hamdan Hamdan; Hapzi Ali (Journal of Law and Humanities Review, 2025)
This study aims to analyze the effect of collaboration strategy and regulation on the competitiveness of legal products and to examine the mediating role of regulation in this relationship. Competition among legal products has become increasingly complex due to the presence of illegal imported goods that do not comply with established standards, safety requirements, and documentation completeness. This research adopts a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to business actors engaged in legal products and were analyzed using SEM-PLS. The results indicate that collaboration strategy has a positive and significant effect on both regulation and competitiveness. Regulation also exerts a positive and significant influence on competitiveness and mediates the relationship between collaboration strategy and competitiveness. These findings confirm that the synergy between strategic collaboration and regulatory effectiveness fosters a conducive market ecosystem, enhances legal compliance, strengthens product standards and safety, and promotes competitive advantage for legal products. The study provides theoretical implications for the development of an integrative collaboration-regulation-competitiveness model, as well as managerial implications for strengthening product legality strategies.